2012
DOI: 10.1007/s10853-012-6414-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of doubly functional nanowhiskers from a colloid solution including a V–Ti complex precursor

Abstract: In this study, we synthesized vanadium (V) nanoparticles precursor (NH 4 ) 5 [(VO) 6 (CO 3 ) 4 (OH) 9 ]Á10H 2 O a two-phase system of toluene and water. Colloid solution including titanium(IV) isopropoxide and polyvinylpyrrolidone (PVP) was subsequently deposited onto the nanoparticles to form urchin-like structures in a toluene solution as the vanadium-titanium (V-Ti) complex precursor. Calcining the urchin-like precursor at 700°C generated nanowhiskers of the Ti/V oxide complex after annealing process. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The O1s and V2p spectra of the two samples were shown in figures 6(c) and 7(c), respectively. The phase of vanadium oxide could typically be determined based on the location of the distinctive V2p3/2 peak, as this is the position most sensitive to the phase transition [41]. As indicated in figures 6(c) and 7(c), the V 2p nuclear peaks in both samples were well-matched to the V 4+ state, indicating that the chemical valence was well-controlled [42].…”
Section: Resultsmentioning
confidence: 98%
“…The O1s and V2p spectra of the two samples were shown in figures 6(c) and 7(c), respectively. The phase of vanadium oxide could typically be determined based on the location of the distinctive V2p3/2 peak, as this is the position most sensitive to the phase transition [41]. As indicated in figures 6(c) and 7(c), the V 2p nuclear peaks in both samples were well-matched to the V 4+ state, indicating that the chemical valence was well-controlled [42].…”
Section: Resultsmentioning
confidence: 98%
“…In the eld of VO 2 -based thermochromic smart windows, TiO 2 is also an important composite layer because of its good compatibility and crystalline structure similar to that of VO 2 . 5 It has been reported that TiO 2 lms are effective underneath layers or cover layers for inducing the crystallization of VO 2 (M/R), 6 constructing heterostructures for photoemission, 7,8 enhancing the oxidation durability, 9,10 regulating the phase transition properties, 11 and improving the optical performance of VO 2 . 1,12 Moreover, VO 2 (M)/TiO 2 composites have their own advantages, not only for increasing visible transmittance but also for modifying the infrared modulation ability.…”
Section: Introductionmentioning
confidence: 99%